2010
DOI: 10.1177/0020715210377154
|View full text |Cite
|
Sign up to set email alerts
|

Usual suspects? Public views about immigrants’ impact on crime in European countries

Abstract: Using data from the 2002/3 module of the European Social Survey project, this study examines the relationship between public views about immigrants' impact on crime and measures of criminal behavior in 21 countries of Europe. The results from hierarchical regression models show that perceptions about immigrants' impact are unaffected by personal experience with crime and by contextual measures such as the homicide rate, prison population rate, and ratio of foreign inmate to non-European foreign population. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 61 publications
7
60
2
5
Order By: Relevance
“…e.g. Quillian (1995), Dustmann and Preston (2001), Semyonov et al (2008), andCeobanu (2010). As noted below, we are able to significantly advance the state of the literature regarding the role of immigrant share in influencing attitudes toward immigration.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…e.g. Quillian (1995), Dustmann and Preston (2001), Semyonov et al (2008), andCeobanu (2010). As noted below, we are able to significantly advance the state of the literature regarding the role of immigrant share in influencing attitudes toward immigration.…”
Section: Introductionsupporting
confidence: 58%
“…This is an important finding because the existing evidence on the salience hypothesis has been decidedly mixed. For example, Quillian (1995), Dustmann and Preston (2001), Semyonov et al (2008), andCeobanu (2010) observe a positive association between the relative size of the foreign population and anti-immigrants attitudes, whereas, Evans and Need (2002), Semyonov et al (2004), Sides and Citrin (2007), Strabac and Listhaug (2008), and Jolly and DiGiusto (2014) find no such relationship. 4 The use of panel estimation techniques in this paper for cross-national comparisons puts this result on firmer econometric footing by reducing concerns over the impact of omitted country-level variables.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparative survey research, for example, has demonstrated that anti-foreigner sentiment is higher in Greece than anywhere else in Europe (Semyonov et al, 2006;Mulcahy, 2011), and that Greeks hold the most negative views on the continent regarding the impact of foreigners on society, including their impact on crime (Semyonov et al, 2012; see also Semyonov et al, 2008;Semyonov and Glikman, 2009;Ceobanu, 2011;Mulcahy, 2011;Swarts and Karakatsanis, 2013;Figgou et al, 2011). Domestic survey research has meanwhile found that Greeks are more likely to favour stricter police treatment for immigrants than for natives, just as they are more likely to favour imprisonment for immigrant offenders than for offenders from other socio-demographic groups (see further Cheliotis and Xenakis, 2011).…”
Section: Political Discourse and Public Attitudes About Immigrantsmentioning
confidence: 99%
“…According to ESS data with questions tapping considerations about the presumed consequences of immigration, respondents are mostly concerned with increasing crime rates in 20 of the 21 European countries (Ceobanu, 2010). However, research focusing on the immigration and crime relationship mainly concentrated on comparing crime rates for immigrant and native populations (Engbersen, van der Leun, & de Boom, 2007;Melossi, 2014;Reid, Weiss, Adelman, & Jaret, 2005), and the impact of ethnic composition on the perceptions of neighbourhood safety (Semyonov, Gorodzeisky, & Glikman, 2012).…”
Section: Immigrants As Threats To Law and Ordermentioning
confidence: 99%